Vanillosmopsis arborea Baker (candeeiro): production and development of seedlings - Cláudia Araújo Marco; Toshik Iarley da Silva; Tainá Macêdo dos Santos; Hernandes Rufino dos Santos; Silvério de Paiva Freitas Júnior; Josyelem Tiburtino Leite Chaves; Maria Denise Rodrigues dos Santos (Acta Agronómica)
The Araripe Plateau attracts an intense anthropic activity that results in the degradation and risk of extinction of native medicinal species such as Vanillosmopsis arborea Baker (candeeiro). The objective of this work was to test the main propagation methods of this species and to evaluate the survival of the seedlings in different environments. With this, two experiments were installed in the headquarters house of IBAMA[1] located in the Araripe National Forest (FLONA), Crato, State of Ceará. The potential of seedling production and stem and root cutting were evaluated, as well as the adaptation of the seedlings to the two environments (experimental area and their natural habitat). The experiments were distributed in a completely randomized design. The number of live cuttings with callus, number of rooted cuttings, weight of fresh and dry matter of roots, leaf persistence, height and survival of the seedlings were also evaluated. More seeds emerged in an open air environment. The cutting type did not affect the analyzed variables. The substrates only affected the number of rooted cuttings, and the soil from FLONA provided the best result. The seedlings developed better in experimental area, indicating that the candeeiro can be explored rationally.